HER2 and BRAF mutation in colorectal cancer patients: a retrospective study in Eastern China - Zhang, Xiangyan; Wu, Jie; Wang, Lili; Zhao, Han; Li, Hong; Duan, Yuhe; Li, Yujun; Xu, Ping; Ran, Wenwen; Xing, Xiaoming (PeerJ, 2020)
Objective To investigate the frequency and prognostic role of the human epidermal growth factor receptor 2 gene (HER2) and BRAF V600E gene mutation in Chinese patients with colorectal cancer (CRC). Methods Clinicopathological and survival information from 480 patients with stage I–III CRC were reviewed and recorded. HER2 amplification was analyzed by immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH), BRAF V600E mutation was tested by IHC and Sanger sequencing. The relationship between HER2 and BRAF V600E mutation status and clinicopathological characteristics and outcomes were determined. Results The amplification of HER2 and BRAF V600E mutation were identified in 27 of 480 (5.63%) and 19 of 480 (3.96%) CRC patients, respectively. HER2 amplification significantly correlated with greater bowel wall invasion (P = 0.041) and more advanced TNM stage (I vs. II vs. III; 0 vs 5.78% vs. 7.41%, P = 0.013). Patients suffering from tumors with poor differentiation had a higher incidence rate of BRAF V600E mutation than those with moderate/well differentiation (7.77% vs 2.92%, P = 0.04). HER2 amplification was an independent prognostic factor for worse disease-free survival (DFS) (HR = 2.53, 95% CI: 1.21–5.30, P = 0.014). Conclusion The prevalence of HER2 amplification and BRAF V600E mutation in stage I–III CRC patients in Chinese was 6% and 4%, respectively, and HER2 amplification appeared to be associated with a worse DFS. More comprehensive molecular classification and survival analysis are needed to validate our findings.
Keywords: Human epidermal growth factor receptor 2 gene; BRAF mutation; Colorectal cancer; Prognosis